مدى توافر القدرات القيادية من وجهة نظر الحعلمين لدى مديري مدارس التعليم ما بعد الأساسي ( دراسة ميدانية لحدارس محافظة البرعيي في سلطنة عمان) - Almarboui Jamal Khalifa Mohammed (Universiti Sains Islam Malaysia, 2024)
This quantitative study discusses the leadership ability among school principals at Al- Buraini Governorate, Oman which affects teachers differently depending upon the principals’ abilities. To ensure the school’s success, its principal must possess traits of the education leaders. This principal has to go beyond the capacities of a traditional manager whose work is limited to the execution of laws and regulations and the application of routine procedures. Also, the principal must always strive for creativity, innovation, innovation in work environment; and able to influence his subordinates to achieve the aspired educational goals. The problem lies in the emerging challenges encountered by the school administration within the educational field, which requires creative efforts and high performance in enabling them to further expand their educational institutions in any circumstances. Therefore, the study aims to identify the most prominent leadership abilities of post-primary school principals; to verify the varying degrees of their leadership abilities; as observed by teachers, due to their different demographic backgrounds. The researcher employed the descriptive-analytical method for this study. The size of the population in-study was 1462, encompassing both male and female teachers. A sample of 287 post-primary school teachers were selected, in accordance to the table proposed by Krejcie and Morgan (1970). The researcher designed a questionnaire that comprised of 60 items distributed over five axes; authority use, awareness of communication principles, the understanding of others, objectivity, and flexibility. Findings revealed that teachers have a high perception of leadership abilities in school principals, in the following order: awareness of communication principles, authority use, understanding of others, objectivity, and flexibility. Moreover, there is a significant statistical difference of (0.05) among the mean scores of the principals’ readiness of leadership abilities, fields of leadership abilities and the overall score. The findings also concluded a statistically significant difference at the level of (0.05) in the areas; awareness with communication principles and objectivity among teachers; in relation to years of experience and benefits to teachers of more than 10 years of experience. In addition, findings also showed a statistical significant difference of (0.05) between the criteria: the school principals’ readiness of leadership abilities, according to the teachers’ perspectives, from the teachers’ experience at different calendar years, that corresponds to the number of years accumulating to more than 10 years.